PERAN KEPALA SEKOLAH UNTUK MENGATASI HAMBATAN GURU DALAM PENGEMBANGAN KURIKULUM MERDEKA DI SEKOLAH DASAR - M Choirul Muzaini; Maemonah; Istiningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The change in the transition period from the 2013 curriculum to the independent curriculum makes several obstacles experienced by the school community, one of which is the teacher in adjusting his competence to the latest curriculum. So that the principal plays a very important role in overcoming these obstacles. The purpose of this study is to reveal the role of the principal to overcome teacher obstacles in developing an independent curriculum in elementary schools. This research uses a case study method through a qualitative approach with Samirono State Elementary School as the location of this research. Data collection techniques were obtained through observation, interviews, and documentation. In an effort to obtain valid data, the data validity test was carried out through data triangulation. Data analysis techniques used were data reduction, data presentation, and data verification. The results of this study show that the role of the principal to overcome teachers' obstacles in developing an independent curriculum in elementary schools is as a decision maker, mentor, liaison, director, leader, and coordinator.